DIGITAL LITERACY IN VOCATIONAL HIGH SCHOOL ENGLISH LEARNING MATERIALS - Ratna Dewanti; Berliana Febri; Dadang Solihat (English Review: Journal of English Education, 2022)
This study aims to investigate digital literacy in vocational high school English learning materials since these schools are supposed to prepare their students for professional world. This qualitative study employs a content analysis method, analyzing the English learning materials used by vocational high schools in Central Jakarta. The words and sentences representing the weaving of digital literacy in 42 English learning materials are the data of this study. Digital literacy indicators covering seven components: information processing, critical thinking and problem solving, communication and collaboration, citizenship, ethics, operation skills and safety are used as the research instruments. The findings indicate that all literacy components but citizenship and safety are incorporated in the materials. They are mostly used in the assignments, followed by the contents and the miscellanies parts of the learning materials. However, despite the existence, they seem to be not evenly incorporated in all components of the materials.